1975
DOI: 10.3758/bf03201452
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation designed to simulate the effects of prisms used in studies of visual rearrangement

Abstract: A system is described which simulates some of the visual rearrangements and changes in sensorimotor relations that occur when experimental subjects move their eyes while looking through a contact lens with a prism attached. The simulated system is more convenient than a system based on the use of a contact lens. and it is based on measures of eye movement that are important in research on the perceptual effects of visual rearrangement. The effects that occur are reviewed in this paper. We also show in detail h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1975
1975
1979
1979

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…However, as noted previously, this latter contention seems at odds with a previous experiment by , the authors (Gourlay, Gyr, Walters, & Willey, 1975). It has also been challenged recently by Craske and Crawshaw (1975) and by Wallach and Halperin (1977).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, as noted previously, this latter contention seems at odds with a previous experiment by , the authors (Gourlay, Gyr, Walters, & Willey, 1975). It has also been challenged recently by Craske and Crawshaw (1975) and by Wallach and Halperin (1977).…”
Section: Discussionmentioning
confidence: 79%
“…A previous experiment by the authors (Gourlay, Gyr, Walters, & Willey, 1975) had shown adaptation to curvature using a similar CRT-simulation methodology and under conditions in which it is unlikely that potentiation could have played a part. Two possibilities for the failure were considered.…”
Section: Discussionmentioning
confidence: 94%
“…Gourlay, Gyr, Walters, and Willey (1975) report a method for accomplishing this which is somewhat similar to the method we employ.…”
Section: Plan Of the Studymentioning
confidence: 92%
“…Instead of using an optical device, it is preferable to produce the desired rearrangement of the visual world by a computercontrolled visual display, the position of which is continuously contingent upon the eye position of the observer. Gourlay, Gyr, Walters, and Willey (1975) report a method for accomplishing this which is somewhat similar to the method we employ.…”
Section: Plan Of the Studymentioning
confidence: 99%
“…H & R accordingly reasoned that shape adaptation, like adaptation to displacement, ought to be inducible by having S experience spatial rearrangement associated with voluntary movement, but that this need not involve direct exposure to actually-rearranged curved or straight lines. It is on this point that the H & R study diverged from the rest of the literature on visual shape adaptation (e.g., Festinger, Burnham, Ono, & Bamber, 1967;Gourlay, Gyr, Walters, & Willey, 1975;Gyr & Willey, 1970;Sirigatti, 1974;Slotnick, 1969;and Victor, 1968). By not training S with actual curved contours, H & R did not need to control for other variables that have plagued the interpretation of many other studies, such as the so-called Gibson effect (Gibson, 1933), which concerns the induction of shifts in the perception of straightness after brief fixation of a curved line.…”
Section: Theoretical Backgroundmentioning
confidence: 99%